Influence of the nanofiber dimensions on the properties of nanocellulose/poly(vinyl alcohol) aerogels. Issue 13 (8th December 2014) - Mueller, Silvana; Sapkota, Janak; Nicharat, Apiradee; Zimmermann, Tanja; Tingaut, Philippe; Weder, Christoph; Foster, E. Johan
ABSTRACT The investigation of aerogels made from cellulose nanofibers and poly(vinyl alcohol) (PVOH) as a polymeric binder is reported. Aerogels based on different nanocellulose types were studied to investigate the influence of the nanocellulose dimensions and their rigidity on the morphology and mechanical properties of the resulting aerogels. Thus, cellulose nanocrystals (CNCs) with low (10), medium (25), and high (80) aspect ratios, isolated from cotton, banana plants, and tunicates, respectively, microfibrillated cellulose (MFC) and microcrystalline cellulose (MCC) were dispersed in aqueous PVOH solutions and aerogels were prepared by freeze‐drying. In addition to the cellulose type, the PVOH‐ and the CNC‐concentration as well as the freeze‐drying conditions were varied, and the materials were optionally cross‐linked by an annealing step or the use of a chemical cross‐linker. The data reveal that at low PVOH content, rigid, high‐aspect ratio CNCs isolated from tunicates afford aerogels that show the least amount of shrinking upon freeze‐drying and display the best mechanical properties. However, with increasing concentration of PVOH or upon introduction of a chemical cross‐linker the differences between materials made from different nanocellulose types decrease. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41740.